Wage Rigidities in Colombia: Measurement, Causes, and Policy Implications - Sonia A. Agudelo; Hector Sala (Institute of Labor Economics (IZA), 2017)
This paper evaluates the extent of wage rigidities in Colombia over a period, 2002-2014, in which the fall in unemployment was relatively slow with respect to sustained economic growth. Following Holden and Wulfsberg (2009), we compute a measure of downward real wage rigidity (DRWR) of 12.09%, four times bigger than their aggregate estimate for the OECD economies. Moreover, in contrast to the evidence for the advanced economies, the determinants of such rigidities show no connection to the wage bargaining system. Amid the absence of effective labor market institutions to make rigidities less prevalent, economic growth appears as the most powerful mechanism to ward them off. Under this light, we provide a stylized description of the wage setting rule in Colombia, compare it with the common one in the advanced economies, and call for a far-reaching reform of the Colombian wage bargaining setup.
Keywords: E24; J3; J48; J58; 330; downward real wage rigidity; wage bargaining; minimum wage; informality; unemployment